2011
DOI: 10.1111/j.1365-3156.2011.02853.x
|View full text |Cite
|
Sign up to set email alerts
|

Burden and outcome of HIV infection and other morbidities in health care workers attending an Occupational Health Program at the Provincial Hospital of Tete, Mozambique

Abstract: Summaryobjectives To investigate the burden and outcome of HIV infection and other morbidities amongst a Mozambican hospital staff.methods Within an occupational health service set up in April 2008 in the provincial hospital of Tete, Mozambique, we offered to all staff members an initial clinical, laboratory and radiological screening and followed them up prospectively until April 2010.results A total of 47.5% of 423 health workers attended the program. The cohort (female-to-male ratio: 2.2; mean age: 39 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The incidence of active TB among HCW at MCH is comparable to the median incidence of 1180/100,000 reported in a meta-analysis of active TB in HCW from high-incidence countries [17]. Similarly, in a study conducted in Tete, Mozambique in 2010, 21% of HCW reported prior TB disease with 2.1% diagnosed with active TB disease at screening or during follow up (incidence not specified) [18]. Therefore, our findings support previous work suggesting occupational risk plays a major role in this setting.…”
Section: Discussionmentioning
confidence: 53%
“…The incidence of active TB among HCW at MCH is comparable to the median incidence of 1180/100,000 reported in a meta-analysis of active TB in HCW from high-incidence countries [17]. Similarly, in a study conducted in Tete, Mozambique in 2010, 21% of HCW reported prior TB disease with 2.1% diagnosed with active TB disease at screening or during follow up (incidence not specified) [18]. Therefore, our findings support previous work suggesting occupational risk plays a major role in this setting.…”
Section: Discussionmentioning
confidence: 53%
“…We also excluded studies focusing on populations of patients not representative of the general population such as miners [17], prisoners [18], healthcare workers [19] or injecting drug users [20].…”
Section: Methodsmentioning
confidence: 99%
“…The explanation could be that the web-based surveys were perceived as more timely and easy to complete. Several other studies using web-based survey also achieved high response rates, ranging from 75% to 96% [ 16 , 17 , 23 ]. However these were in high income countries where availability and use of web-based systems are widely utilised, which is not the norm in SA.…”
Section: Discussionmentioning
confidence: 95%
“…However, the higher prevalence may also be driven by a result of selection bias in the current study, where people with TB may be more motivated to complete the survey and share their experience. However, a study done in Mozambique during April 2008 –April 2010 identified a prevalence of 21% (42/201) among HCWs in an occupational health program [ 23 ]. Another study in KwaZulu-Natal from January 2006 to December 2010, using record reviews in three district hospitals, found a prevalence among HCWs of 9% (112/1,313) [ 26 ], which is the same as the current study.…”
Section: Discussionmentioning
confidence: 99%